Universal health coverage for inclusive and sustainable development : lessons from Japan - Ikegami, Naoki, 1949- (World Bank study., 2014)
The goals of universal health coverage (UHC) are to ensure that all people can access quality health services, to safeguard all people from public health risks, and to protect all people from impoverishment due to illness, whether from out-of-pocket payments for health care or loss of income when a household member falls sick. Countries as diverse as Brazil, France, Japan, Thailand, and Turkey have shown how UHC can serve as a vital mechanism for improving the health and welfare of their citizens and lay the foundation for economic growth and competitiveness grounded in the principles of equity and sustainability. Ensuring universal access to affordable, quality health services will be an important contribution to ending extreme poverty by 2030 and boosting shared prosperity in low-income and middle-income countries, where most of the world's poor live. Universal Health Coverage for Inclusive and Sustainable Development synthesizes the experiences from 11 countries-Bangladesh, Brazil, Ethiopia, France, Ghana, Indonesia, Japan, Peru, Thailand, Turkey, and Vietnam-in implementing policies and strategies to achieve and sustain UHC. These countries represent diverse geographic and economic conditions, but all have committed to UHC as a key national aspiration and are approaching it in different ways. The book examines the UHC policies for each country around three common themes: (1) the political economy and policy process for adopting, achieving, and sustaining UHC; (2) health financing policies to enhance health coverage; and (3) human resources for health policies for achieving UHC. The findings from these country studies are intended to provide lessons that can be used by countries aspiring to adopt, achieve, and sustain UHC. Although the path to UHC is specific to each country, countries can benefit from the experiences of others in learning about different approaches and avoiding potential risks.